Effectiveness of educational interventions in minimizing reactance in traffic accident prevention - von Beesten, Silke; Bresges, André; Lubert, Daniela (Frontiers in Education, 2024)
This study explores the effectiveness of exhibiting a damaged car along with structured instruction in achieving road safety goals. Participants engage with the damaged car, discussing the extent of deformation due to excessive speed. Role simulations prompt participants to imagine and address risky traffic situations. However, a strong fear appeal may lead to reactance, where the audience rejects the message, resulting in unintended behavior, known as the boomerang effect. To mitigate this, emotional appeals should be accompanied by solution-focused, action-oriented, and self-esteem-building interventions. The study employs Design-Based-Research to develop targeted learning opportunities for knowledge acquisition and transfer into everyday life. It adapts methods from cognitive behavioral therapy and traffic safety programs for a follow-up to emotionalizing prevention campaigns. The research examines changes in participants' norms, values, and attitudes. Findings suggest reactance effects after emotionalizing campaigns, and the structured post-survey influences behavior. The presence of police officers does not significantly impact reactive behavior. The follow-up tool may apply to various emotionalizing prevention campaigns. Future research will focus on students' physics literacy development during the analysis of accident blackspots in traffic spaces.